2017
DOI: 10.1111/jpn.12724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo feeding of L‐arginine on the development of digestive organs, intestinal function and post‐hatch performance of broiler embryos and hatchlings

Abstract: SummaryThis study was to investigate the effects of in ovo feeding (IOF) L-arginine (Arg) solution on the development of digestive organs, the duodenal mucosa of broiler embryos and hatchlings, and the growth performance of chicks during the first week post-hatch.A total of 720 fertilized eggs with similar weight were randomly allocated to three groups, consisting of eight replicates of 30 eggs each. Three treatments were arranged as non-injected control, diluent-injected (0.75% NaCl solution) group and Arg so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…The results from this study are consistent with other researches, which have shown that in ovo injection of arginine did not affect hatchability of neonatal Turkey poults or chicks (Foye et al, 2007;Gao et al, 2018). The results from this study are consistent with other researches, which have shown that in ovo injection of arginine did not affect hatchability of neonatal Turkey poults or chicks (Foye et al, 2007;Gao et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results from this study are consistent with other researches, which have shown that in ovo injection of arginine did not affect hatchability of neonatal Turkey poults or chicks (Foye et al, 2007;Gao et al, 2018). The results from this study are consistent with other researches, which have shown that in ovo injection of arginine did not affect hatchability of neonatal Turkey poults or chicks (Foye et al, 2007;Gao et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In a different study, in ovo injection of 1% l-arginine increased body weight gain of chicks during seven days post-hatching period (Gao et al, 2018). In a different study, in ovo injection of 1% l-arginine increased body weight gain of chicks during seven days post-hatching period (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study showed that the yolk sac residue decreased in broiler embryos and chickens from 19 E to 3 day post‐hatch (Gao, Zhao, Li, et al., ). Similar pattern was observed in all treatments in the present study from 19 E to 3 day of age.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, these sources may not be sufficient to support embryonic development (Uni et al, ; Shafey, Al‐Batshan, Al‐Owaimer, & AL‐Samawei, K. A., ). In ovo feeding (IOF), developed to overcome amino acid limitations in these sources, has enhanced poultry embryo intestinal functionality, the nutritional status of hatchlings, poult quality, post‐hatch development and survivability (Uni et al, ; Foye et al, ; Gao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BCAAs, and especially isoleucine, have a key role in the upregulation of intestinal and muscular glucose transporters and in enhancing glucose consumption and utilization (Zhang et al, ). Therefore, the IOF of BCAAs may accelerate embryo growth and hatching time by reducing muscle protein mobilization for gluconeogenesis and by promoting muscle development under normal physiological conditions during the perinatal period (Bhanja & Mandal, ; Bai, Greene, Li, Kidd, & Dridi, ; Gao et al, ). In poultry liver Commission Internationale de l'Eclairage (CIE) L*, a* and b* (CIELab) values, L* (lightness) that varies with diet and feeding level represents a normal physiological condition and is associated with energy metabolism (Trampel, Sell, Ahn, & Sebranek, ; Kop‐Bozbay & Ocak, ).…”
Section: Introductionmentioning
confidence: 99%